Not to be missed : fifty-four favorites from a lifetime of film - Turan, Kenneth (PublicAffairs, 2014)
"As a child in 1950s Brooklyn, Kenneth Turan often turned to television programs like "Million Dollar Movie" on WOR-TV. Featuring a much-loved theme song from Gone with the Wind, "Million Dollar Movie" would run one feature film twice a day, every day, all week. It was there that he developed a life-long love of the world of the movies. One of the most discerning critics writing today, in his latest book Kenneth Turan offers insights that are sure to delight and inspire movie-lovers of all kinds. As sophisticated and illuminating as the films they discuss, Turan's sketches are a blend of cultural analysis, historical anecdote, sordid Hollywood controversy, and astute critical appraisals, all suffused with his abiding love for the silver screen. Turan's favorite films range across all genres, low and high. From All About Eve to Seven Samurai to Spirited Away, these are now timeless films--classic and contemporary, familiar and obscure, with big budgets and small--each as interesting as the lives of the authors and actors that made the usually two-or-so-hour-long cinematic experience itself"--